Jumuo Namaayi - Koyukuo village (Lawra District), Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Jumuo Namaayi is a farmer from the village Koyukuo in Ghana. He describes how the rainy season has changed over the last few years and and its effects on the crops and fruit production. The fruits often don't ripen in time and diseases are more frequent he explains. This is causing villagers to migrate towards the south. A response has been to include new seed varieties that grow faster, introduced to him by the Ministry of Food and Agriculture (AGRIC).